Malaria specific mortality in lowlands and highlands of Muheza district, north-eastern Tanzania - Kamugisha, M L; Gesase, S; Mlwilo, T D; Segja, B P; Minja, D T; Massaga, J J; Msangeni, H A; Ishengoma, D R; Lemnge, M M; Mmbando, B P (Tanzania Journal of Health Research, 2007)
Vital registration of causes of death in Tanzania is incomplete and many deaths occur outside health caresettings. Verbal autopsies (VA) are used to determine the underlying cause of death, and the probable diagnosis helps toestimate reasonably cause-specific mortality. In this paper, we report findings of a verbal autopsy survey which involvedeight villages in both low and highlands of Muheza district, north-eastern Tanzania. The survey was conducted followinga rapid census, which was done to identify households that had lost one or more members within a period of two yearsfrom the date of census. Trained research assistants administered VA questionnaires to parents/close relatives. Two physiciansreviewed each report independently and a third opinion was sought where there was discordant report between the two. Atotal of 9,872 households were surveyed and 134 deaths were recorded. A total of 96 (71.6%) deaths were from lowlandvillages representing high malaria transmission. Majority (72.4%) of the reported deaths occurred at home whilst 32.1%occurred at heath facility settings. Overall, severe malaria was the leading cause accounting for 34.3% of all deaths. Infantswere most affected and accounted for 43.5% of the total deaths. Pulmonary tuberculosis ranked second (8.2%) cause ofdeaths and was exclusively confined to individuals ≥15 years. Probable cause of death could not be determined in 13.4%of deaths. In conclusion, majority of deaths in rural north-eastern Tanzania occur at home and the immediate causes areusually unknown or not documented. These findings indicate that the verbal autopsy is a useful tool for detecting leadingcauses of death at community level in the absence of health facility-based data. Keywords: verbal autopsy, malaria, mortality, lowland, highland, Tanzania Tanzania Health Research Bulletin Vol. 9 (1) 2007: pp.32-37